THE STUDY OF THE CONSERVATION OF SPECIFIC ACTIVITY AND STABILITY OF PROPERTIES OF COMPLEX FUNCTIONAL FOOD PRODUCT «BIOLACT» DURING THE STORAGE - Garbar, S.A.; Fomenko, M.V.; Ten, O.A.; Balpanov, D.S. (Eurasian Journal of Applied Biotechnology, 2014)
The functional food product «Biolakt», consisting of a probiotic consortium of fermented milk cultures Bifidobacterium bifidum, Lactobacillus bulgaricus and Lactobacillus acidophilus was selected as an object for research. We have conducted the studies to determine the number of viable cells, and their antagonist activity and moisture content of the product at different stages of storage. Antagonistic activity of probiotic consortium was studied by the method of agar blocks by submerged way. The culture Staphylococcus aureus was used as the test culture. The amount of viable cells during storage of the probiotic consortium was determined by limiting dilution on a nutrient medium Blaurock for the growth of probiotic Bifidobacterium bifidum culture and semisolid nutrient medium №1 for the growth of lactic acid cultures Lactobacillus bulgaricus and Lactobacillus acidophilus. The study of the microbiological purity of the drug at different storage periods was determined by microscopic control and seeding on a number of culture media (MPA, MPB). Moisture content was determined by the method of drying up to constant mass at a temperature of (100-105)°C in a laboratory baker. The data on the study of conservation of specific activity and stability of characteristics during the storage were submitted. . The practical significance of the work is in the introduction of the technology of producing functional food product, preserving the biological activity within 3-6 months into production.